Visual Review of Periodic Print Media Advertising in Bandung, West Java 1970 Decade - Heryadi, Heddy (Universitas Ciputra, 2017)
Since Dutch plantation owners in West Java established and developed the city of Bandung, they settled in the area of the city and also making periodical print media for socialization and communication among them. In the past 1930 decade the Dutch colonial start to create and form the printed media and publications in a steady and continuous way in West Java. After the independence declaration of Indonesia State in 1945, the print media and periodical publications continued and remade by the Chinese and indigenous communities. The area of Bandung became more advanced into a business city after World War II, in which formed commercial enterprises and other social activities. During the period of Indonesia government shifting from “orde Lama” to “orde baru” the activities of printing and publishing as a network of communication media increasingly established and widely established. In West Java, newspapers and magazines such as;